The preparation Neurexan® for the treatment of anxiety disorders in multimorbid patients. Resolution of the Council of Experts - Nataliya A. Ermolenko; Valeriya A. Bykova; Olga V. Ulyanova; Lyudmila V. Tribuntseva; Olga V. Troshina (LLC "MEDIAFORMAT", 2023)
Stress disorders are a global public health problem, having a significant impact on patients and society. Chronic stress can lead to long-term consequences, including mental and physical illness. The body's first response to acute stress is characterized by the appearance of anxiety, but beyond a certain level, anxiety becomes maladaptive. Anxiety worsens the quality of life and adaptation of patients, complicates the course of comorbid pathology and its diagnosis. In the review anxiety disorders in patients with multiple sclerosis, Parkinson's disease, and chronic pain syndromes discussed. A significant deterioration in the course and prognosis of the neurological disease in combination with anxiety disorders in multimorbid patients has been shown. Treatment of anxiety includes psychotherapy, the use of antidepressants, and short courses of benzodiazepines. Neurexan® as the safe and effective drug that does not interact with other drugs and has a favorable tolerability profile can be recommended to patients with multimorbid pathologies to correct emotional disorders, reduce anxiety and improve sleep.